INTERFERENSI GRAMATIKA BAHASA INDONESIA KE DALAM BAHASA PRANCIS OLEH PEMBELAJAR BERBAHASA INDONESIA - Tobing, Roswita Lumban; Wijana, I Dewa Putu ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this study is to explain the grammatical interference of Indonesian language to French, found in the students writings of semester II, III and IV students, at Faculty of Languages and Arts, Yogyakarta State University. The research data are collected from the students French essays. The interference analysis is based on a structural and functional approach. The structural approach is used to look at the rules of standard language and the functional approach is used to look at the function. The contrastive analysis method is applied to explain the grammatical systems differences between Indonesian and french languages, producing the interference. The contrastive analysis method is applied to describe the forms of interference. The research findingss showed that the syntactic interferences occur on (1) the phrases level, namely: (a) the noun phrases, (b) the adjective phrases, (c) verbal phrases, (d) adverbial phrases, and (e) prepositional phrases, (2) the clause level, namely: (a) adjective construction as an attrributive subject in the clause, (b) the construction of the pronoun as a direct object, (c) the construction of the pronoun as an indirect object, (d) the construction of the pronoun as a direct and indirect object used simultanously, (e) the construction of pronoun 'yâ and âen' as an adverb, and (f) the structure pattern of passive voice. The interference of Indonesian to French noun and adjective phrases can be identified in the omition of suffix (feminine and plural) for nouns and adjectives in French, ie. omition the suffix {-e} to denote the feminine, suffix {-s} for plural marker, and the suffix {-es} to denote the plural adjectives for feminine-plural nouns. The formation of a noun phrase and an adjective phrase adjusting to the type and number of nouns in French grammatical rules effects the interference. In Indonesian language, there are neither genre of noun nor the adjective, there is no noun accordance. Plural marker is done by adding the plural marker lexicon (number). Verbal interference occurs in a conjugation system that should be tailored to the subject and time as well as the modes of the sentence. The conjugation system of the verbe is unknown in Indonesian language. The verbal Interference occurred when the conjugated verbs are not adapted to the subject, the time and mode of the sentences. Prepositional phrase interferences are caused by the differences of the rules. French preposition usage is adapted to the type, named place of destination, and number of nouns (the destination). Instead the use of prepositions in Indonesian language is not adapted to the type, the name of the destination, and the number of nouns (the destination). The clause level interference occurs in the use of the personal pronoun of direct and indirect object. In Frence language, the object pronouns (direct and indirect) in the clause is always put in front of the verbs with the pattern: COD + V, while Indonesian structure is V + O. This is why the interferences occur, by applying the structure of the Indonesian language to the French structure. The interference on the use of adverb pronoun y and en occurs because the used of Indonesian adverb pronouns is different with the used of adverb pronouns in French. This is one of the difficulties for students when they use both of these adverbs pronouns in a sentence, so that they interfere the rules that they have mastered (in Indonesian) into French.